1983
DOI: 10.1161/01.hyp.5.4_pt_2.ii97
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the hypotensive effects of calcium antagonists.

Abstract: The antihypertensive efficacy of monotherapy with the calcium antagonists nifedipine (n = 60) and verapamil (n = 43) was investigated in patients with essential hypertension. Relationships between age, pretreatment blood pressure, pretreatment plasma renin activity, and hypotensive response were examined. Intraindividual differences in the responses to both drugs were also studied (n = 16). Treatment with verapamil had to be discontinued because of constipation in one patient; treatment with nifedipine was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
2

Year Published

1985
1985
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(38 citation statements)
references
References 0 publications
4
32
2
Order By: Relevance
“…Other studies have demonstrated (Weber & Drayer, 1984;Ruddel et al, 1984;Buhler et al, 1982) that the antihypertensive efficacy varies from patient to patient. In contrast to other studies (Muller et al, 1984;MacGregor et al, 1982;Erne et al, 1983), we found no statistically significant correlation between pretreatment blood pressure level and the degree of blood pressure response. The short half-life of nitrendipine (Aronoff & Sloan, 1985;Goa & Sorkin, 1987) and the low dosage used may explain the reduced antihypertensive efficacy at 3 h compared with that at 1 h after drug administration.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have demonstrated (Weber & Drayer, 1984;Ruddel et al, 1984;Buhler et al, 1982) that the antihypertensive efficacy varies from patient to patient. In contrast to other studies (Muller et al, 1984;MacGregor et al, 1982;Erne et al, 1983), we found no statistically significant correlation between pretreatment blood pressure level and the degree of blood pressure response. The short half-life of nitrendipine (Aronoff & Sloan, 1985;Goa & Sorkin, 1987) and the low dosage used may explain the reduced antihypertensive efficacy at 3 h compared with that at 1 h after drug administration.…”
Section: Discussioncontrasting
confidence: 99%
“…15 Conversely, dietary salt loading in two hypertensive rat strains dramatically increased dihydropyridine receptors. 16 Furthermore, the clinical antihypertensive effect of another type of calcium channel blocking drug, verapamil, is also enhanced in low renin hypertensive individuals, 4 and the longer-term antihypertensive efficacy of nifedipine may also be predicted by initial serum ionized calcium levels. 17 Finally, the present study suggests the importance of in vivo calcium transport in mediating the tightly coupled renin-induced stimulation of adrenal aldosterone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, calcium channel blocking agents were found to lower pressure preferentially in lower renin forms of experimental as well as human hypertension. 3 - 4 We would similarly predict that differing initial levels of extracellular calcium would also affect the hypotensive efficacy of calcium blocking drugs. However, no studies to date have related clinical indices of calcium metabolism to the effects of these agents.…”
mentioning
confidence: 99%
“…Efficacy and tolerability of nicardipine 141S apy for the treatment of essential hypertension (Gould et al, 1983;Erne et al, 1983). They have been reported to be well tolerated and to lack many of the side-effects of other popular anti-hypertensive drugs, such as the biochemical disorders associated with thiazide diuretics (Amery et al, 1978;Grimm et al, 1981) or the side effects of lethargy, cold extremities, and bronchospasm following,B-adrenoceptor antagonists (Besterman, 1983).…”
Section: Discussionmentioning
confidence: 99%